Opportunities in The Midst of Uncertainties / Fadhirul Hisham Aziz and Farihah Hassan - Aziz, Fadhirul Hisham; Hassan, Farihah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Since pandemic Covid-19 hit Malaysia with the first Movement Control Order (MCO) being announced in March 2020, things have changed globally, including Malaysia. Conventional ways of doing things can be regarded as obsolete, and those who are still practicing it might face severe difficulties if the mindset remains the same. However, there are silver linings seen from the impacts of the pandemic. We can see that there are changes that have been implemented whether in the government, businesses, people, and others. From the government's perspective, specifically the education system, the way of teaching and learning has totally changed. Online learning platforms available are fully utilized to ensure continuity and avoid disruption in a student’s learning process. Some of the best online learning platforms including Google Meet and Classroom, Cisco WebEx, Microsoft Teams, and others, have given opportunities to lecturers to explore and experiment with new ways of delivering knowledge. The trial and error process, which may be exhaustive, will eventually produce the best outcomes on conveying the information to the students.